The journey of mesothelioma: from postmortem to FNA. (10th February 2014) - Gorecka, M; Scott, J; Casey, R; Breen, D
Abstract : A 73-year-old man, non-smoker presented with an 8-week history of left-sided chest pain and shortness of breath on exertion. He had no significant medical history. He worked in construction for 40 years, but denied definite asbestos exposure. His initial chest X-ray demonstrated a large left-sided pleural effusion. Subsequent CT thorax revealed circumferential thickening of the pleura with associated pleural plaques and calcification. A provisional diagnosis of mesothelioma was made. Initial ultrasound-guided thoracocentesis revealed a transudate with negative cytology. In addition, thoracoscopy and CT-guided pleural biopsy failed to obtain a definitive diagnosis. A surgical biopsy was planned, but at the time of admission, the patient developed unilateral neck swelling. Ultrasound-guided fine-needle aspiration (FNA) and core biopsies of the lymph node were diagnostic for pleural mesothelioma. Treatment with palliative chemotherapy was planned, but the patient's clinical status rapidly deteriorated and he passed away prior to the beginning of therapy.